Engineering SpyCatcher Variants with Proteolytic Sites for Less‐Trace Ligation. Issue 2 (19th December 2018) - Zhang, Xue‐Jian; Wu, Xia‐Ling; Liu, Dong; Da, Xiao‐Di; Wang, Xiao‐Wei; Yang, Shuguang; Zhang, Wen‐Bin
Summary of main observation and conclusion: The SpyTag/SpyCatcher reaction is a powerful tool for bioconjugation, but it leaves a complex of considerable size after ligation. To facilitate removal of the catalytic fragment, proteolytic recognition sites (such as DDDDK, AVLQ, and WELQ) were directly engineered into the first or second loop of SpyCatcher at locations after the reactive lysine to give a set of cleavable SpyCatcher variants. Among them, SpyCatcher DDDDK exhibits excellent reactivity with SpyTag and could still be cleaved proteolytically by enterokinase after ligation. Notably, SpyCatcher DDDDK is disordered in solution and forms an ordered complex upon reaction with SpyTag with a second order rate constant of 99.2 ± 0.1 M –1 ·s –1, which is comparable to, if not faster than, most click reactions. The results demonstrate the high sequence plasticity of SpyCatcher and suggest that covalent bond formation may confer robustness on the folded structure against extensive mutation. These variants add to the expanding toolbox of genetically‐encoded peptide‐protein chemistry with diverse features. Abstract : SpyCatcher variant with engineered proteolytic site allows efficient reaction and facile cleavage of the catalytic fragment after coupling, enabling less‐trace ligation.